Triboelectric hydrophone for underwater detection of low-frequency sounds. (August 2022) - Liu, Jing; Liu, Mingyang; Sun, Chenchen; Lin, Zhiwei; Feng, Zhiping; Si, Shaobo; Yang, Jin
Abstract: A hydrophone is the core part of sonar and plays an important role in underwater acoustic detection applications. However, there is still room for hydrophones to improve their ability to detect low-frequency signals in their fabrication, dimensions, sensitivity, and types. This study presents an innovative triboelectric hydrophone (TH) for high-sensitivity detection of underwater low-frequency sound. The TH consists of a hemispherical shell, an acoustic coupling agent, and a multi-layer membrane triboelectric nanogenerator (TENG). When utilizing the acoustic impedance matching among water, the shell, and the coupling agent, sound waves could easily penetrate the waterproof shell into the coupling agent. Then, the sound waves can be received and converted into electrical signals by the TENG. The TH has the characteristics of a working frequency ranging from 30 Hz to 800 Hz and a heart-shaped directional pattern. The receiving sensitivity of the TH is greater than − 192 dB in the frequency range from 150 Hz to 500 Hz, which offers remarkable sensitivity to low-frequency sounds. With these capabilities, the TH is demonstrated for detecting underwater sounds generated by objects falling and other sources. The results indicate that the exploration of TENG-based underwater acoustic devices offers a promising avenue for the development of hydrophones. Graphical Abstract: A triboelectric hydrophone (TH) was designed to detect underwater low-frequency sounds. Different from conventional hydrophones, the TH use triboelectric nanogenerator as the conduction mechanism. The TH has a working frequency ranging from 30 Hz to 800 Hz and a heart-shaped directional pattern. ga1 Highlights: The TH provides a wide working frequency bandwidth (30–800 Hz). The sensitivity of the TH is higher than that of a standard hydrophone (RHS-30) in the frequency range of 150–500 Hz. The TH shows excellent performance in underwater acoustic detection, such as hitting the tank wall events and the impacts of a falling mass.